2,3-Bis(4-ethoxyphenyl)quinoxaline - Ping-Ping Ye; Cai-Li Zhang; Zhi-Qiang Du (Acta Crystallographica Section E, 2010)
The title compound, C24H22N2O2, was prepared by condensation of 1,2-bis(4-ethoxyphenyl)ethane-1,2-dione and 1,2-diaminobenzene. The asymmetric unit contains one half-molecule, close to a twofold axis. The plane of the quinoxaline ring is twisted with respect to the planes of the two ethoxyphenyl ring systems, exhibiting dihedral angles of 39.95 (9)°. The crystal packing is dominated by weak C—H...π interactions. No classical hydrogen bonds or stacking interactions are observed.